The mediating effect of reading on the relationships between awareness, perception and attitude towards satisfaction with IIUMToday Campus Newspaper / Aini Maznina Abdul Manaf and Saodah Wok. - Abdul Manaf, Aini Maznina; Wok, Saodah (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2018)
IIUMToday, established on May 1, 2014, is the official campus newspaper for International Islamic University Malaysia (IIUM). It is operated by students under the jurisdiction of the Department of Communication. To test the level of satisfaction in reading it, the objectives of the study are (1) to determine the degree of agreement to reasons for visiting the IIUMToday website, awareness of, perception of, attitude toward, reading habit of, and satisfaction with IIUMToday among students in the IIUM; (2) to examine the awareness of, perception of, attitude toward, reading habit of, and satisfaction with IIUMToday among the students in IIUM; (3) to test the relationships among awareness, perception, attitude and reading habit with satisfaction; and (4) to determine the mediating effect of the reading habit of IIUMToday among students on their satisfaction. The study used the quantitative research design, employing the survey method with the questionnaire as the research instrument for data collection. A total of 104 respondents were found to be readers of IIUMToday. Results show that there exist moderate levels of awareness, perception, attitude, reading habit, and satisfaction with IIUMToday. The relationships among the variables concerned are significantly positive. In addition, reading habit partially mediates the relationship between the predictors and the criterion.